Obstructive Giant Inflammatory Polyposis: Is It Related to the Severity or the Duration of the Inflammatory Bowel Disease? Two Case Reports - Antoine Abou Rached; Jowana Saba; Leila El Masri; Mary Nakhoul; Carla Razzouk (Case Reports in Gastrointestinal Medicine)
We report two cases of giant inflammatory polyposis (GIP) with totally different presentation and evolution. The first patient had two giant pseudopolyps after one year of the diagnosis of UC. The second patient had one obstructive giant pseudopolyp secondary to CD at the level of the transverse colon, being totally asymptomatic years before the presentation. GIP is a rare complication of inflammatory bowel disease (IBD). It consists of numerous filiform polyps that look like a “mass of worms” or a “fungating” mass. Surgical resection is inevitable when GIP presents with obstructive symptoms.